Self-reported prevalence of low back pain in Estonian rowers - Arend, M.; Akel, J.; Haabpiht, L.; Jürgenson, J. (Acta Kinesiologiae Universitatis Tartuensis, 2016)
The aim of this study was to determine the lifetime prevalence and point prevalence of low back pain (LBP), the related pain intensity and the rowing-related aggravating factors for LBP in Estonian rowers. A total of 78 rowers (38 female and 40 male subjects) completed a single questionnaire at the start of the competitive rowing season to determine lifetime and point prevalence, pain intensity and rowing-related LBP aggravating factors. The lifetime prevalence was high in both male and female rowers (90% and 93%, respectively), and the reported point prevalence of LBP was 10% in males and 21.1% in females. Female rowers reported significantly higher (p=0.02) LBP intensity when training 7-16 hours per week, when compared to females whose training volume was less than six hours per week. Rowing-related LBP aggravated factors were long rowing workouts, weight training and sitting for a long period of time. LBP is highly prevalent in rowers and female rowers seemed to be more prone to developing higher intensity LBP when training loads increased. Coaches should cooperate more with sports medicine specialists to better prepare female athletes core endurance to tolerate longer duration rowing workouts and prevent LBP.